Sizing AC/DC building distribution network part I - Yang, Ming (Nanyang Technological University, 2020)
Renewable energy source such as solar PV panels become emerging in the energy market. Moreover, the amount of DC loads such as computers, electric vehicles and electronic devices is increasing in our homes. Therefore, AC/DC distribution network is proposed and studied due to its capabilities that can reduce large numbers of power converters and enhance energy efficiency. Instead of investigating all the types of residential buildings, an HDB block is chosen as HDB block is the most representative residential building in Singapore. In this study, the AC/DC distribution network is designed, AC source is utility grid and DC source is solar power. By analyzing the data from EMA and other sources, building’s electrical loads are classified as AC&DC loads and maximum demand for system are calculated. Solar panels are proposed at roof and maximum solar power is calculated base on area and weather. Battery energy storage system is designed to supply energy to this building during peak hours. The sizes of battery converter, main AC/DC converter and PV converter are determined by the voltage and power of the designed system.